Ecossistemas digitais na saúde : transformações na pandemia e a implementação do Conecte SUS - Isabela Crispim Brito Furtado (2022)
This dissertation discusses the digital transformations in the context of the pandemic, especially in the field of health and in Brazilian government services. The debate focuses on the implications of platformization on health, as well as the inflections of the health emergency on the platformization of everyday life, highlighting the process of implementing the Conecte SUS program. At the intersection between digital, health and the state in the context of Covid, the program is announced by the Federal Government as the health platform of the Sistema Único de Saúde (SUS) and is analyzed in this work from 2020 to 2021. Based on the influence of platform studies, the research is guided by an investigation in three dimensions: on the structuring of the ecosystem in which Conecte SUS is integrated, the dissemination made in program bulletins published on the Ministry of Health website, and the security vulnerabilities, such as data leaks, cyber attacks and other information inconsistencies that affected the reliability and quality of the information provided. The research findings corroborate the literature of platform studies, since the intensification of digitalization processes in the field of health impacts on the way the body, health, safety, public and private can be reconfigured from digital dynamics. In addition, the analysis of the implementation of Conecte SUS points to important contributions on how the governance of and on the platforms operate in the Brazilian context, especially in the national regulation of services that integrate international connectivity infrastructures and digital ecosystems in health.